Tinjauan Hukum Terkait Keuangan Negara di Lingkup BUMN Persero Serta Penyelesaiannya Terhadap Problematika Tindak Pidana Korupsi - Yudiastari, Rike Hevi (El-Dusturie, 2022)
Legal review regarding the status of state finances within the scope of state-owned enterprises and the resolution of the problems of corruption, which uses a type of normative legal research which uses a statutory approach, and legal history, as well as legal politics, that there are research results which find that first , positive laws such as the 1945 Constitution and the package of state finance laws have provided legal certainty regarding the status of state finances within the SOE Persero environment as state finance, which for the sake of creating a governance mechanism and an accountable, transparent, prudent state financial accountability in the end will create prosperity for all people. There is a consequence that all legal arrangements that are different and raise doubts must still refer to the provisions of the 1945 Constitution and the package of laws on state finances. Second, regulation regarding the legal status of finance within the BUMN Persero regarding the problem of state losses in the problem of resolving a criminal act of corruption in which the directors and commissioners of a Persero BUMN can be subject to criminal charges of corruption (besides civil and administrative) if in the management of state finances within the BUMN Persero , the decisions and actions fulfill the elements of the offense regulated in Article 2 paragraph (1) and Article 3 of Law no. 31 of 1999 jo. UU no. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption, without having to prove beforehand whether there are state losses caused by these decisions and actions. This is based on good will to save state finances in order to increase the country's economic growth and the welfare of all the people.Tinjauan hukum terkait status keuangan negara di lingkup BUMN Persero serta penyelesaian terhadap problematika tindak pidana korupsi, yang mana menggunakan jenis penelitian hukum normatif yang mana menggunakan pendekatan perundang-undangan, dan sejarah hukum, serta politik hukum, Bahwa terdapat hasil penelitian yang mana menemukan bahwa pertama, hukum positif seperti UUD 1945 dan paket undang-undang keuangan negara telah memberikan kepastian hukum tentang status keuangan negara di lingkungan BUMN Persero sebagai keuangan negara, yang mana demi menciptakan mekanisme tata kelola dan suatu pertanggungjawaban keuangan negara yang akuntabel, transparan, penuh kehatihatian, yang pada akhirnya akan menciptakan kesejahteraan bagi seluruh rakyat. Terdapat suatu Konsekuensi yang mana segala pengaturan hukum yang berbeda dan menimbulkan keraguan harus tetap mengacu pada ketentuan dalam UUD 1945 dan paket undang-undang keuangan negara. Kedua, pengaturan tentang status hukum keuangan di lingkup BUMN Persero terhadap problematika kerugian negara pada masalah penyelesaian suatu tindak pidana korupsi yang mana bahwa direksi dan komisaris BUMN Persero dapat dikenai tuntutan pidana korupsi (selain perdata dan administrasi) jika dalam pengelolaan keuangan negara di lingkungan BUMN Persero, keputusan dan tindakannya memenuhi unsur-unsur delik yang diatur dalam Pasal 2 ayat (1) dan Pasal 3 Undang-Undang No. 31 Tahun 1999 jo. UU No. 20 tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi, tanpa harus dibuktikan terlebih dahulu ada tidaknya kerugian negara yang diakibatkan oleh keputusan dan tindakan tersebut. Hal ini didasarkan pada good will untuk menyelamatkan keuangan negara demi meningkatkan pertumbuhan perekonomian negara dan kesejahteraan seluruh rakyat